2018
DOI: 10.1590/0074-02760170385
|View full text |Cite
|
Sign up to set email alerts
|

NS1 codon usage adaptation to humans in pandemic Zika virus

Abstract: BACKGROUND Zika virus (ZIKV) was recognised as a zoonotic pathogen in Africa and southeastern Asia. Human infections were infrequently reported until 2007, when the first known epidemic occurred in Micronesia. After 2013, the Asian lineage of ZIKV spread along the Pacific Islands and Americas, causing severe outbreaks with millions of human infections. The recent human infections of ZIKV were also associated with severe complications, such as an increase in cases of Guillain-Barre syndrome and the emergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The link between Zika virus and severe malformations of the central nervous system (particularly microcephaly) has been demonstrated by many studies in Brazil and has been reported retrospectively in French Polynesia [48] . Genetic differences between African and Asian/American strains of Zika virus and appearance of the ‘pathogenic clone’ may explain the emergence of Zika virus infections in South America and Asia [48] , [49] .
Fig.
…”
mentioning
confidence: 99%
“…The link between Zika virus and severe malformations of the central nervous system (particularly microcephaly) has been demonstrated by many studies in Brazil and has been reported retrospectively in French Polynesia [48] . Genetic differences between African and Asian/American strains of Zika virus and appearance of the ‘pathogenic clone’ may explain the emergence of Zika virus infections in South America and Asia [48] , [49] .
Fig.
…”
mentioning
confidence: 99%
“…The abrupt variation observed in ZIKV population sizes over time could be correlated to the rapid increase of available sequencing data [ 64 ] and to the recent wide distribution of ZIKV from the Pacific Islands to the Americas [ 30 , 31 , 32 , 33 ]. The high NS1 CAI values of the Asian genotype for the human genome confirmed in this study were associated with the Asian genotype ZIKV for humans [ 65 ].…”
Section: Discussionmentioning
confidence: 60%
“…This clearly shows that the African genotype ZIKV also has the potential to efficiently replicate in humans. This is particularly true for the CAI for the E and NS5 proteins [ 65 ], which have a major role in flaviviruses replication and virulence [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation pressure, the external environment, selective transcription, and natural selection are listed as factors that determine codon usage bias. As with other RNA viruses [58][59][60][61], CDV depends on the host susceptibility with respect to survival and transmission. Thus, the CDV codon usage pattern may interact with the virus' ability to infect, adapt, and escape from the host immune responses.…”
Section: Discussionmentioning
confidence: 99%